The molecular landscape of glioma in patients with Neurofibromatosis 1 - D'Angelo, Fulvio; Reuss, David (Nature medicine, 2019)
An integrated analysis of glioma samples from patients with neurofibromatosis 1 annotates their mutational, epigenetic, transcriptional, and immunological features and uncovers similitudes with a subset of sporadic gliomas.
Published: 10 December 2018
Gesehen am 02.08.2019